A review of remote sensing applications in flower phenology detection - Ehsan Rahimi; Chuleui Jung (Journal of Ecology and Environment)
The shift in flowering phenology with plants blooming earlier due to climate change, disrupts the synchronization between plants and pollinators by creating temporal and spatial mismatches. Monitoring these shifts is essential, and remote sensing has become an invaluable tool for detecting flowering periods over vast areas. Despite the technological advancements, there remains a significant gap in comprehensive reviews that explore the use of remote sensing in flowering phenology and its impact on pollination ecology. Therefore, this study aims to review and summarize research on the remote sensing of flowers, with a particular focus on key techniques used to analyze flowering phenology. We categorized the application of remote sensing in the field of flowering phenology into four groups based on the type of data used: optical, Synthetic Aperture Radar (SAR), Unmanned Aerial Vehicle (UAV), and PhenoCam-based applications. In each section, we have reviewed and provided a summary of the studies conducted in this field, with a particular focus on those that primarily examine canola crop flowering. In conclusion, our findings reveal that Optical remote sensing, proves effective in capturing detailed imagery of flowering events, while SAR technology offers robust, all-weather monitoring capabilities. UAV-based remote sensing provides high-resolution, site-specific data, although it is constrained by operational limitations. PhenoCams offer valuable long-term monitoring but lack the spatial resolution for detailed analysis. Each remote sensing approach has distinct advantages and limitations, underscoring the need for integrated methods to improve flowering phenology assessments and enhance agricultural monitoring.